The high-speed rail project as an urban redevelopment tool - Carmen Bellet Sanfeliu; Luis Santos Ganges (Belgeo)
In Spain, several local councils have taken advantage of the arrival of high-speed rail to rethink the whole railway system within the city. These rail transformations have caused major urban changes and have also been accompanied by property development projects that were planned during the economic expansion of the 1990s and first decade of 2000s, prior to the arrival of the economic crisis in 2008. The combination of these factors has resulted in some of the most important urban renewal and redevelopment projects ever planned in Spain. This has been the case in two large intermediate cities: Valladolid (303,905 inhabitants in 2015), located on the northwest HSR line, which received new services in 2007, and Zaragoza (664,953 inhabitants in 2015), located on the Madrid-Barcelona-French border HSR line, where the new train service arrived in 2003. In Spain, the introduction of HSR services has been accompanied by certain specific issues relating to their initial conception, subsequent management and associated governance; these are illustrated in the article through case studies of Valladolid and Zaragoza.